2009
DOI: 10.1270/jsbbs.59.47
|View full text |Cite
|
Sign up to set email alerts
|

A novel mutant gene for (1-3, 1-4)-.BETA.-D-glucanless grain on barley (Hordeum vulgare L.) chromosome 7H

Abstract: (1-3, 1-4)-β-D-glucan contained in barley (Hordeum vulgare L.) grains is a main component of endosperm cell walls and constitutes the cell wall matrix with arabinoxylan. A monofactorial recessive mutant gene for (1-3, 1-4)-β-D-glucanless grain was found and the new gene was designated as bgl (= (1-3, 1-4)-beta-Dglucanless grain). A linkage was found between the bgl gene and the naked caryopsis (nud) gene, and it was mapped to the centromeric region of chromosome 7H. Phenotypes in bgl cosegregated with the poly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
49
0
1

Year Published

2009
2009
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(53 citation statements)
references
References 40 publications
2
49
0
1
Order By: Relevance
“…Thinner cell walls and a softer grain texture were also detected in the line with the mutant allele at the HvCslF6 locus 26 . The low beta-glucan character from Chalky Glenn was crossed into a waxy starch background 21 giving rise to barleys lines with waxy starch, but relatively low levels of β-glucan.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…Thinner cell walls and a softer grain texture were also detected in the line with the mutant allele at the HvCslF6 locus 26 . The low beta-glucan character from Chalky Glenn was crossed into a waxy starch background 21 giving rise to barleys lines with waxy starch, but relatively low levels of β-glucan.…”
Section: Discussionmentioning
confidence: 95%
“…More recently, a number of cellulose synthase-like genes have been identified and implicated in the synthesis of β-glucan 12 and several of these genes have been located on the barley genome and sequenced. This has created the potential to identify and exploit mutations that suppress synthesis and Tanooka et al 26 reported a 'β-glucanless' grain, resulting from a mutation in the HvCslF6 locus on chromosome 7H. Hull-less barley, adapted to UK growing conditions, also became available with the release of the variety Penthouse and initial studies on distilling potential indicated that it was of at least moderate quality 3 .…”
Section: Introductionmentioning
confidence: 99%
“…After this time, only CSLF6 has significant levels of expression throughout the developing endosperm, suggesting that this gene is responsible for the accumulation of (1→3, 1→4)-b-D-glucan during differentiation. Indeed, the barley blg [(1,3;1,4)-b-D-glucan less] mutant that has a mutation within the HvCSLF6 gene lacks (1→3, 1→4)-b-D-glucan in both endosperm and aleurone walls (Tonooka et al, 2009), confirming that this is the major gene contributing to (1→3, 1→4)-b-D-glucan content within the grain. Reduction of CSLF6 gene expression in wheat using RNA interference constructs has shown that this gene is also a major contributor to wheat endosperm cell wall (1→3, 1→4)-b-D-glucan (Nemeth et al, 2010).…”
Section: Cellulosementioning
confidence: 99%
“…It is the most highly expressed CSLF gene in most tissues of barley (Hordeum vulgare), wheat (Triticum aestivum), Brachypodium distachyon, and rice (Oryza sativa), including developing seedling leaf, coleoptiles, and endosperm (Burton et al, 2008;Kimpara et al, 2008;Doblin et al, 2009;Nemeth et al, 2010;Pellny et al, 2012;Vega-Sánchez et al, 2012;Suliman et al, 2013;Trafford et al, 2013;Schreiber et al, 2014). When CSLF6 expression is reduced either by knockdown or knockout via mutation or T-DNA insertion (Tonooka et al, 2009;Nemeth et al, 2010;Taketa et al, 2012;Vega-Sánchez et al, 2012;Hu et al, 2014), a significant reduction in MLG is observed in both vegetative and floral tissues, indicating its gene product is responsible for the synthesis of the majority of MLG in grasses.…”
Section: Introductionmentioning
confidence: 99%